MODELLING AGILE-TRANSFORMATION ORGANIZATIONAL DEVELOPMENT PROJECT PORTFOLIO - S. Bushuyev (Astana IT University, 2021)
Agile transformation is a necessary process for companies in various fields of activity to ensure their competitiveness in modern business conditions when the uniformity of production processes and the growth of the level of customer (client) demands reduce the impact of traditional ones that remain competitive. Modern business is a «customer-oriented» business, in which instead or in addition to technological or marketing advantages comes the highest value of human resources and teamwork. That means Agile transformation provides companies with a transition to another level, and those who have not moved to this level remain outside of competitiveness, if not in the near term, then in a strategic perspective. Agile transformation is comparable to the need to intro-duce new technologies into production processes to replace obsolete ones since, without new technological solutions, the products created do not meet modern quality requirements or do not have a competitive cost price. Thus, Agile transformation ensures the introduction of new technology not only into the production process but into the management system and product creation processes within the framework of the project or project-oriented activities